Lebanese Blonde - Geha, Joseph (Book collections on Project MUSE., 2012)
Lebanese Blonde takes place in 1975-76 at the beginning of Lebanon's sectarian civil war. Set primarily in the Toledo, Ohio, "Little Syria" community, it is the story of two immigrant cousins: Aboodeh, a self-styled entrepreneur; and Samir, his young, reluctant accomplice. Together the two concoct a scheme to import Lebanese Blonde, a potent strain of hashish, into the United States, using the family's mortuary business as a cover. When Teyib, a newly arrived war refugee, stumbles onto their plans, his clumsy efforts to gain acceptance raise suspicion. Who is this mysterious "cousin," and what dangers does his presence pose? Aboodeh and Samir's problems grow still more serious when a shipment goes awry and their links to the war-ravaged homeland are severed. Soon it's not just Aboodeh and Samir's livelihoods and futures that are imperiled, but the stability of the entire family.